COST-EFFECTIVENESS ANALYSIS OF ANTIBIOTIC USAGE IN DIABETIC FOOT ULCUS PATIENTS IN DOKTER SOEKARDJO TASIKMALAYA HOSPITAL - RAHAYUNINGSIH, NUR; PRATIWI, ALLFI LAILLA; PEBIANSYAH, ANISA (International Journal of Applied Pharmaceutics, 2022)
Objective: Diabetic foot ulcers is sores on the skin surface until it penetrates the skin layer caused by infection, which is require high costs for treatment. This puts a considerable burden on the patient's family, health agencies and society in general. The purpose of this study was to describe the direct medical costs and cost-effective antibiotics for diabetic foot ulcer patients at Dokter Soekardjo Tasikmalaya Hospital. Methods: The research method is retrospectively with a purposive sampling technique. The research subjects included 24 hospitalized diabetic foot ulcer patients who received antibiotic treatment ceftriaxone with metronidazole or meropenem with metronidazole. The effectiveness of therapy was determined by the Length of Stay (LOS). Direct medical costs were obtained from medical costs, treatment costs, laboratory costs, and radiology costs. Results: The average direct medical cost for the combination of ceftriaxone and metronidazole antibiotics was Rp. 4 668 062 and for the combination of meropenem antibiotics with metronidazole was Rp. 9 093 830. The effectiveness of the antibiotic ceftriaxone with metronidazole was 47%. Conclusion: The cost-effective antibiotic was ceftriaxone with metronidazole which has the lowest ACER value Rp. 9 932 046 and the ICER value is Rp. 22 128 840.